Alpha-1-antitrypsin as novel substrate for S. aureus’ Spl proteases – implications for virulence - Scherr, Franziska; Darisipudi, Murthy N.; Börner, Friedemann R.; Austermeier, Sophie; Hoffmann, Franziska; Eberhardt, Martin; Abdurrahman, Goran; Saade, Christopher; von Eggeling, Ferdinand; Kasper, Lydia; Holtfreter, Silva; Bröker, Barbara M.; et al. (Frontiers in Immunology, 2024)
BackgroundThe serine protease like (Spl) proteases of Staphylococcus aureus are a family of six proteases whose function and impact on virulence are poorly understood. Here we propose alpha-1-antitrypsin (AAT), an important immunomodulatory serine protease inhibitor as target of SplD, E and F. AAT is an acute phase protein, interacting with many proteases and crucial for prevention of excess tissue damage by neutrophil elastase during the innate immune response to infections.MethodsWe used MALDI-TOF-MS to identify the cleavage site of Spl proteases within AAT’s reactive center loop (RCL) and LC-MS/MS to quantify the resulting peptide cleavage product in in vitro digestions of AAT and heterologous expressed proteases or culture supernatants from different S. aureus strains. We further confirmed proteolytic cleavage and formation of a covalent complex with Western Blots, investigated AAT’s inhibitory potential against Spls and examined the NETosis inhibitory activity of AAT-Spl-digestions.ResultsSplD, E and F, but not A or B, cleave AAT in its RCL, resulting in the release of a peptide consisting of AAT’s C-terminal 36 amino acids (C36). Synthetic C36, as well as AAT-SplD/E/F-digestions exhibit NETosis inhibition. Only SplE, but not D or F, was partly inhibited by AAT, forming a covalent complex.ConclusionWe unraveled a new virulence trait of S. aureus, where SplD/E/F cleave and inactivate AAT while the cleavage product C36 inhibits NETosis.